Structural evolution of Si-50%C powder during mechanical alloying and heat treatment - 汤文明 郑治祥 吴玉程 徐光青 吕珺 刘君武 王建民 (Transactions of Nonferrous Metals Society of China, 2008)
The nanocrystalline β-SiC powder was successfully synthesized by ball milling the Si-50%C elemental powder. During ball milling, a solid solution of C in Si, Si（C）, firstly forms, followed by SiC. The formation of SiC is controlled by the mixing mechanism of the gradual diffusion reaction（GDR） and the mechanically induced self-propagating reaction（MSR）. The amount of β-SiC increases with milling time increasing. After 40 h milling, there exists only β-SiC in the milled powder. The grain size of β-SiC is about 6.4 nm after the powder is milled for 60 h. After the 60 h-milled Si-50%C elemental powder is heat treated at 1 100℃for l h, the grain size of β-SiC does not change, but the lattice ordering degree offl-SiC increases.